Fas gene promoter –670 polymorphism in gynecological cancer. (1st January 2006) - Ueda, M.; Terai, Y.; Kanda, K.; Kanemura, M.; Takehara, M.; Yamaguchi, H.; Nishiyama, K.; Yasuda, M.; Ueki, M.
Abstract : Single-nucleotide polymorphism at −670 of Fas gene promoter (A/G) was examined in a total of 354 blood samples from normal healthy women and gynecological cancer patients. They consisted of 95 normal, 83 cervical, 108 endometrial, and 68 ovarian cancer cases. Eighty-three patients with cervical cancer had statistically higher frequency of GG genotype and G allele than 95 controls ( P = 0.0353 and 0.0278, respectively). There was no significant difference in the genotype or allele prevalence between control subjects and endometrial or ovarian cancer patients. The Fas −670 GG genotype was associated with an increased risk for the development of cervical cancer (OR = 2.56, 95% CI = 1.08–6.10) compared with the AA genotype. The G allele also increased the risk of cervical cancer (OR = 1.60, 95% CI = 1.05–2.43) compared with the A allele. Germ-line polymorphism of Fas gene promoter −670 may be associated with the risk of cervical cancer in a Japanese population.